(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The research basically aimed to analyse the effect of isolated, complex weight and plyometric training on anaerobic power. Sixty male students studying at the Department of Physical education, Annamalai University, Annamalainagar, Chidambaram were randomly selected as. The selected subjects were divided into four equal groups of fifteen subjects each, such as weight training group, plyometric training group and control group. The group I underwent weight training program and group II underwent plyometric training program for three days per week for twelve weeks, group III underwent weight training for first six weeks and plyometric training for remaining six weeks. And Group IV categorized belonged to the control group who were not allowed to participate in any special training program but for the regular Physical education classes as required by the curriculum. Anaerobic power was the predetermined criterion variable. All the four groups were tested on the selected dependent variable both predetermined pre and post training. After establishing significance at 0.05 level of confidence as per the ‘F’ ratio for the adjusted posttest of the paired mean differences, the analysis of covariance was used to analyze the significant difference. The Scheffe’s test to find out the paired mean differences, if any. The .05 level of confidence was fixed as the level of significance to test the ‘F’ ratio obtained by the analysis of covariance, which was considered as an appropriate. Through the results of the present study it can be stated as there existed significant difference among the selected groups- weight training group, plyometric group, complex weight training and the control group in aerobic power.